2017
DOI: 10.1039/c6cp07539h
|View full text |Cite
|
Sign up to set email alerts
|

Simulated photoelectron intensities at the aqueous solution–air interface for flat and cylindrical (microjet) geometries

Abstract: Ion spatial distributions at the aqueous-air/vacuum interface are accessible by energy-dependent X-ray photoelectron spectroscopy (XPS). Here we quantify the difference between a flat surface and a cylindrical shaped microjet on the energy-dependent information depth of the XPS experiment and on the simulated photoelectron intensities using solutions of pure water and of 1 mol/L NaI as examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Therefore, when detecting electrons coming from all around the jet, the total spectrum should essentially be a weighted sum of spectra obtained for different angles of the polarization relative to a semi-innite at-surface. 50 However, we found that this polarization direction did not have an important inuence on the simulated spectra, at least when compared to the effects that we demonstrate in this work. Here, we show simulated spectra for three cases, corresponding to 0, 45 and 90 orientations of the polarization.…”
Section: Appendix Cgeometry Approximationscontrasting
confidence: 42%
See 3 more Smart Citations
“…Therefore, when detecting electrons coming from all around the jet, the total spectrum should essentially be a weighted sum of spectra obtained for different angles of the polarization relative to a semi-innite at-surface. 50 However, we found that this polarization direction did not have an important inuence on the simulated spectra, at least when compared to the effects that we demonstrate in this work. Here, we show simulated spectra for three cases, corresponding to 0, 45 and 90 orientations of the polarization.…”
Section: Appendix Cgeometry Approximationscontrasting
confidence: 42%
“…Indeed, the portion of the jet facing the incoming light has this polarization parallel to the surface, while the portion facing the skimmer has it orthogonal to the surface, and all intermediate cases exist. Therefore, when detecting electrons coming from all around the jet, the total spectrum should essentially be a weighted sum of spectra obtained for different angles of the polarization relative to a semi-infinite flat-surface [50]. However, we found that this polarization direction did not have an important influence on the simulated spectra, at least when compared to the effects that we demonstrate in this work.…”
Section: Appendix C -Geometry Approximationsmentioning
confidence: 49%
See 2 more Smart Citations
“…The AWI is modeled as an atomically flat interface (average emission angle = 0°) following the finding of our recent work, 36 which revealed that the jet curvature has a negligible effect on the ion intensity ratio. The atomic-density profiles obtained from MD simulations are used as input for the sample geometry after coarse graining them into wider bins, since the number of possible layers in SESSA is limited to 54.…”
Section: ■ Methodsmentioning
confidence: 99%